ANALISIS PENGARUH KURS, SERTIFIKAT BANK INDONESIA DAN INFLASI TERHADAP KINERJA REKSADANA PENDAPATAN TETAP TAHUN 2015-2019 - Andini Nurwulandari (FEBI UIN Sunan Gunung Djati Bandung, 2020)
Each type of investment has different risks. However, the general rule is that the higher the likelihood of an investment the greater the risk of the instrument. This study uses a qualitative method with a descriptive analysis approach. The data source is secondary data from the official BI website. OJK and BPS. This research covers all OJK mutual funds between 2015-2019. Sampling was done purposively. Data documentation is used for sampling. The results of the study found that the level of development has a negative effect on the results of fixed-income mutual funds, the lower the SBI, the worse the output of mutual funds that have fixed income will be; and inflation does not affect the FIM, because inflation represents a continuous increase in costs for products and services.